Gastroesophageal reflux disease is associated with a more severe interstitial lung disease in systemic sclerosis in the EUSTAR cohort - Roth, Eliane; Bruni, Cosimo; Petelytska, Liubov; Becker, Mike Oliver; Dobrota, Rucsandra; Jordan, Suzana; Mihai, Carina; Muraru, Sinziana; Carreira, Patricia E.; De Vries-Bouwstra, Jeska; Braun-Moscovici, Yolanda; Liakouli, Vasiliki; et al. (Rheumatology, 2025)
Objectives: Gastroesophageal reflux disease (GERD) is frequent in systemic sclerosis (SSc) and could predict progression of interstitial lung disease (ILD). We aimed to analyse (1) the prevalence of GERD among SSc-ILD patients, (2) its association with disease characteristics and (3) predictive factors for ILD progression in SSc-ILD patients with GERD. Methods: SSc patients from the EUSTAR database with ILD were included. GERD was labelled as present if reflux/dysphagia was reported at the baseline visit or before. Disease characteristics of patients with and without GERD were compared at baseline. ILD progression was defined as relative FVC decline ≥10% or relative FVC decline between 5–9% in association with relative DLCO decline of ≥15% over 12 ± 3 months of follow-up. Prognostic factors for ILD progression, overall survival and progression-free survival in SSc-ILD patients with GERD were tested by multivariable Cox regression. Results: A total of 5462 SSc-ILD patients were included, 4400 (80.6%) had GERD. Patients with GERD presented more frequently with diffuse cutaneous SSc (OR: 1.44 [1.22–1.69], P < 0.001) and more severe lung involvement with lower FVC (85.8 ± 22.1 vs 90.2 ± 20.1, P < 0.001), lower DLCO (60.8 ± 19.7 vs 65.3 ± 20.6, P < 0.001) and worse performance at the 6-min walking test. Female sex (HR: 1.39 [1.07–1.80], P ¼ 0.012) and older age (HR: 1.02 [1.01–1.03], P < 0.001) independently predicted ILD progression in SSc-ILD patients with GERD. Conclusion: SSc-ILD patients with GERD appear to suffer from a more severe SSc disease. In this population, female sex may be considered a risk factor for ILD progression.
CRIS-Team Scopus Importer:2025-12-19
Keywords: gastroesophageal reflux disease; interstitial lung disease; progression; systemic sclerosis